An Industrial systems design study on Reneur Research and Development Institute (RRDI) - Boyonas, Mark Ismael; Claridad, Ma. Lourdes Bernadette; Generalao, Lynn Mae; Nepomuceno, Larissa (College of Engineering, 2003)
Reneur Research and Development Institute (RRDI) is a manufacturing company engaged in the production of herbal products, such as shampoo, soap, lotion and deodorant. 60% of their products are exported to countries like United States, Korea, Qatar and Malaysia. This study will tackle 5 problem areas which were identified by the group using the stream diagnostic diagram. These are: no medium-to-long term vision/plans, inefficient plant layout and inventory system, not-well-defined job functions, and no waste disposal management. All these problems were examined thoroughly and alternatives were generated and evaluated. The evaluation of the Strengths, Weaknesses, Opportunities and Threats facing the company was the basis of the formalization of the corporate and marketing strategies of the firm. In formalizing these strategies a formal medium to long term master-plan is presented. In this way a clear picture of the future plans and direction of the company is drafted. This will be the very basis of any forward-looking decisions that the company will make. Key corporate operational policies have been suggested, like environmental, manufacturing and distribution policies. Relocating to the new plant site in Amparo Village, Quezon City was recommended. The proposed RRDI compound will have the following facilities: Solids and Liquids Manufacturing Facilities, Raw material and finished goods warehouses, an extraction area, housing accommodations for employees and the main office. With the transfer, a new and efficient layout was presented. Furthermore, the new plant site can accommodate the future expansion, if ever the company decides to do so. The problems identified in the area of workforce management are: a) Not well-defined job functions and responsibilities and b) No performance appraisal. Both areas for improvement cause inefficient employees. The creation of a new organizational structure, well defined job descriptions, and the establishment of a performance appraisal system were recommended to address the problems in workforce management. The problem with having no waste disposal management could be improved by implementing composting, recycling and waste separation. Composting is the natural decomposition of solid biodegradable wastes while recycling is the re-manufacture of soap scraps. Waste separation is the process of separating the water used in cleaning the equipment from the first rinsing from the succeeding rinsing. These recommendations will result in proper disposal of approx. 100kg of solid biodegradable wastes, additional income from the re-manufacture of soap scraps and approx 50% savings in water consumption.